Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Rút gọn các biểu thức sau :

Rút gọn các biểu thức sau :

a) \(\left( {x + 2} \right)\left( {x - 2} \right) - \left( {x - 3} \right)\left( {x + 1} \right)\) ;

b) \({\left( {2x + 1} \right)^2} + {\left( {3x - 1} \right)^2} + 2\left( {2x + 1} \right)\left( {3x - 1} \right)\) .

Hướng dẫn làm bài:      

a) \(\left( {x + 2} \right)\left( {x - 2} \right) - \left( {x - 3} \right)\left( {x + 1} \right) \)

=\( {x^2} - {2^2} - \left( {{x^2} + x - 3x - 3} \right)\)

=\({x^2} - 4 - {x^2} - x + 3x + 3\)

=\(2x-1\)  ;

b) \({\left( {2x + 1} \right)^2} + {\left( {3x - 1} \right)^2} + 2\left( {2x + 1} \right)\left( {3x - 1} \right)\)

=\({\left( {2x + 1} \right)^2} + 2.\left( {2x + 1} \right)\left( {3x - 1} \right) + {\left( {3x - 1} \right)^2}\)

=\({\left[ {\left( {2x + 1} \right) + \left( {3x - 1} \right)} \right]^2}\)

= \({\left( {2x + 1 + 3x - 1} \right)^2}\)

=\({\left( {5x} \right)^2} = 25{x^2}\)